Integrating 3C3R and 4C/ID frameworks to optimize problem-based learning in cell biology in secondary education - Eka Trisianawati; Handi Darmawan; Mustika Sari; V. Prawnya; Noviansyah Kusmahardhika (University of Muhammadiyah Malang, 2026)
Background: Problem-Based Learning (PBL) promotes higher-order thinking, but in cell biology its implementation often produces cognitive overload because students must coordinate abstract organelle structures, invisible intracellular processes, and interconnected metabolic pathways across multiple representations. Existing studies rarely integrate structured problem design and task sequencing to address these specific cognitive demands. This study addressed that gap by combining the 3C3R and 4C/ID frameworks within a PBL environment. Objective: This study aimed to develop and evaluate an integrated PBL-3C3R-4C/ID instructional model for cell biology in terms of validity, practicality, and effectiveness in managing students’ cognitive load. Methods: Using a Research and Development approach based on Hannafin and Peck, followed by a pretest-posttest control group design, the study involved 231 secondary school students. Cognitive load was measured through a multidimensional scale covering intrinsic, extraneous, and germane load. Data were analyzed using descriptive statistics and paired t-tests. Results: The model demonstrated high validity and strong reliability (α = 0.91). Post-intervention results showed significant improvement in learning outcomes, accompanied by reduced extraneous load and increased germane load. Conclusion: Integrating 3C3R and 4C/ID within PBL offers a theoretically grounded and empirically supported approach for teaching complex cell biology while managing students’ working memory demands more effectively.